PERANCANGAN ARSITEKTUR BERKELANJUTAN PADA GEDUNG SERBA GUNA KHUSUSNYA UNTUK ISOLASI DARURAT DENGAN MENGGUNAKAN KAMAR PORTABLE PINTAR DI JAKARTA BARAT - Andika Putra; Anggraeni Dyah; Dody Kurniawan (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
The goal to be achieved in the design of the application of sustainable architecture in the design of a multi-purpose building as an emergency isolation room using a smart portable room is to produce an isolation facility for someone who is exposed to Covid-19 and can be used in emergency areas. Designing a Multipurpose Building as an Emergency Isolation Room using a Sustainable Architecture concept approach. Provide Emergency Isolation facilities for someone who has been exposed to Covid-19. The Multipurpose Building as a place for Emergency Isolation, which is an emergency quarantine facility in West Jakarta, has the aim of accommodating patients exposed to Covid-19 who do not get an isolation place at the local hospital. In addition, to help reduce the risk of spreading the Covid-19 virus to family members at home.The Multipurpose Building as a place for Emergency Isolation, which is an emergency quarantine facility in West Jakarta, has the aim of accommodating patients exposed to Covid-19 who do not get an isolation place at the local hospital. In addition, to help reduce the risk of spreading the Covid-19 virus to family members at home.